Expression of endoglin, CD105, in conjunctival melanocytic nevi: Is it suspicious like in thyroidology? Oculi plus vident quam oculus? - Detanac,Dzenana (2022)
SUMMARY Objective: The aim of this study was to evaluate the expression of endoglin and its correlation with histopathological and clinical findings in conjunctival nevi. Methods: The study included archival formalin-fixed, paraffin-embedded tissue sections of 44 patients with conjunctival nevi. Immunohistochemical staining for CD105 had been performed with monoclonal mouse antihuman CD105 antibodies. The intratumoral microvessel density for quantification of tumoral vascularization had been determined by this marker. Results: The expression of CD105 was positive in 30 (68.2%) cases. There was a statistically significant difference in the level of CD105 expression regarding the histological type of nevus (p=0.03) and intralesional cysts status (p=0.02). Spearman's rho (ρ −0.316) revealed a significant negative correlation between the expression of endoglin and the histological type of nevus (p=0.03) and between the expression of endoglin and the presence of intralesional cysts (ρ −0.380, p=0.01). Conclusion: This study suggests that endoglin could be a useful diagnostic and prognostic marker in differentiating between benign and malignant melanocytic ocular lesions.